2018
DOI: 10.1016/j.heliyon.2018.e00548
|View full text |Cite
|
Sign up to set email alerts
|

Early Archean origin of heterodimeric Photosystem I

Abstract: When and how oxygenic photosynthesis originated remains controversial. Wide uncertainties exist for the earliest detection of biogenic oxygen in the geochemical record or the origin of water oxidation in ancestral lineages of the phylum Cyanobacteria. A unique trait of oxygenic photosynthesis is that the process uses a Type I reaction centre with a heterodimeric core, also known as Photosystem I, made of two distinct but homologous subunits, PsaA and PsaB. In contrast, all other known Type I reaction centres i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 58 publications
2
35
0
Order By: Relevance
“…Cardona, 2018;Magnabosco et al, 2018;Shih, Hemp et al, 2017;. Our results support this view, yet at the same time they highlight the great antiquity of photosynthesis by showing that some of the early duplications of the core reaction center proteins likely predate the MRCA of each of the known groups of phototrophs by a large span of time.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Cardona, 2018;Magnabosco et al, 2018;Shih, Hemp et al, 2017;. Our results support this view, yet at the same time they highlight the great antiquity of photosynthesis by showing that some of the early duplications of the core reaction center proteins likely predate the MRCA of each of the known groups of phototrophs by a large span of time.…”
supporting
confidence: 83%
“…Mirroring the evolution of Type II reaction centers, a molecular clock study on Type I reaction centers showed that the duplication event that led to the heterodimerization of the core of Photosystem I was also more likely to be the oldest node after the root (Cardona et al, 2012). This duplication event is widely accepted to have been an evolutionary adaptation to oxygenic photosynthesis (Ben-Shem, Frolow, & Nelson, 2004;Hohmann-Marriott & Blankenship, 2008;Rutherford et al, 2012) and was found to predate the earliest diversification event of anoxygenic Type I reaction centers (Cardona, 2018); namely, the divergence of the reaction center of Heliobacteria from that which gave rise to those in phototrophic Chlorobi and Acidobacteria.…”
Section: An Extended C-terminus and The Mn 4 Cao 5 Cluster Binding mentioning
confidence: 99%
“…This also increases the availability of oxygen for oxygen-dependent metabolic pathways like pigment synthesis (Fujita, Tsujimoto, & Aoki, 2015). In fact, maximum oxygen levels measured in pseudomats in freshwater medium under eCO 2 rO 2 atmosphere came close to (G. violaceus; Supporting Information Figure S3b) or exceeded (C. thermalis; Supporting Information Figure S2b) the oxygen saturation point of freshwater cultures exposed to present-day levels of oxygen, stressing the importance of reactive oxygen species (ROS)-detoxifying mechanisms having to have evolved prior to the GOE (Case, 2017;Cardona, 2018).…”
Section: Combined Observationsmentioning
confidence: 88%
“…Chlorophyll-based photosynthesis is generally accepted to have originated in bacteria in an anoxic environment (Hohmann-Marriott & Blankenship, 2011). The evolution of a heterodimeric photosystem I reaction centre, found in all oxygenic phototrophs today, is thought to have evolved as a protection mechanism against the formation of reactive oxygen species more than 3.4 Ga (Cardona, 2018), necessitating the evolution of protective antioxidant systems (Sheng et al, 2014;Case, 2017). The energy released from the decomposition of water by photosystem I is higher than any other redox couple potentially used during anoxic photosynthesis and could be used to form organic molecules for growth and storage (Hohmann-Marriott & Blankenship, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This is clearly seen in the structures of the photosystems, as Photosystem II not only has retained greater sequence and structural symmetry at the core, but also greater structural identity with Type I reaction centres (Figure 1 and 2). In a manner similar to Type II reaction centres, by studying the rates of evolution I have also found that the gene duplication leading to the heterodimeric core of cyanobacterial Photosystem I has a pretty good chance to have occurred before the diversification event leading to the different groups of phototrophs with homodimeric Type I reaction centres known today (Cardona 2018).…”
Section: Primitive Photosynthesismentioning
confidence: 96%